Promising clinical outcome after body gamma knife radiotherapy for mediastinal follicular dendritic cell sarcoma with thoracic spine invasion and iliac metastasis: A case report and literature review - Hu, Annan; Chen, Ting; Dong, Jian (Frontiers in Oncology, 2022)
Background: Follicular dendritic cell sarcoma (FDCS) is a rare type of low-grade tumor. Mediastinal FDCS with spinal invasion has not been well described. The treatment options include surgical resection and radiation therapy. The body gamma knife is a stereotactic body radiotherapy (SBRT) technology that is widely used in China. The pathological evaluation of a bone lesion after a body gamma knife procedure has not been reported. Here, we report a case of a patient with FDCS with thoracic spine invasion and iliac metastasis treated with surgery and body gamma knife. Case summary: A 36-year-old male patient was hospitalized at Zhongshan Hospital, Fudan University, due to a gradually aggravated pain on the lateral side of the left scapula for 6 months. Imaging examination showed neoplastic lesions on the left side of C7-T2 invading the vertebral body of T1, T2, and caput costae of the second rib, and suspected metastasis in the left ilium. FDCS was diagnosed after performing a computed tomography (CT)-guided core needle biopsy, and the thoracic lesion was surgically resected. The body gamma knife was used as an adjuvant radiotherapy for the thoracic lesion and a primary therapy for the left ilium lesion. Iliac bone lesion resection was performed at Zhongshan Hospital, Fudan University, 2 months after RT. Compared with the biopsy report, the body gamma knife treatment resulted in a pathological complete response (PCR). The magnetic resonance imaging (MRI) examinations showed stable disease of the thoracic lesion after body gamma knife radiosurgery. Conclusion: This case report describes the treatment of mediastinal FDCS with thoracic spinal invasion and iliac metastasis. The promising outcome suggests that separation surgery is an effective treatment option for mediastinal FDCS with spinal column invasion. It also demonstrates the application prospects of the body gamma knife treatment in malignant lesions of the axial bones.